1974
DOI: 10.1039/p29740001318
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of 2-formyl-, 2-acetyl-, and 2 benzoyl-pyrroles

Abstract: Experimental dipole moments (1 03*p/C m) and molar Kerr constants [l 027703(mK2)/m5 V-2 mol-l] are reported for the following as solutes in cyclohexane at 25" : 2-formylpyrrole, 4.33, +76 ; 2-acetylpyrrole, 3.98, +50 ; and 2benzoylpyrrole, 4.06, +42. The results are analysed to provide information concerning the preferred conformations of these molecules.THE conformational preferences of heteroaromatic aldehydes and ketones are continuing to attract much attention. Various physical methods have been applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This confirms earlier experimental results. The conformational preferences of some heteroaromatic aldehydes and their N -methyl derivatives were recognized previously on the basis of various physical methods: 1 H, 13 C NMR, measurements of dipole moments, molar Kerr constants, ab initio studies, and IR spectral investigations. , These studies showed a very strong preference for the s-cis arrangement of the N−H and CO groups. Furthermore, it was demonstrated that for PC-NMe the s-cis conformer is a dominant form (95%). , The IR spectroscopic investigations 1,4 revealed the presence of one absorption band for the free carbonyl group.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…This confirms earlier experimental results. The conformational preferences of some heteroaromatic aldehydes and their N -methyl derivatives were recognized previously on the basis of various physical methods: 1 H, 13 C NMR, measurements of dipole moments, molar Kerr constants, ab initio studies, and IR spectral investigations. , These studies showed a very strong preference for the s-cis arrangement of the N−H and CO groups. Furthermore, it was demonstrated that for PC-NMe the s-cis conformer is a dominant form (95%). , The IR spectroscopic investigations 1,4 revealed the presence of one absorption band for the free carbonyl group.…”
Section: Resultsmentioning
confidence: 87%
“…The calculated dipole moments for eight analyzed structures are also presented in Table 1. In all cases, the dipole moments are lower for the s-cis form, in which the component dipoles of the pyrrole ring and the carbonyl group 12 are in the antiparallel arrangement.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations